Analisa Kualitas dan Kuantitas Biogas dari Kotoran Ternak - Mara, Made; Alit, Ida Bagus (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2011)
Our life is completely dependent on a reliable and adequate supply of energy. In other to reduce dependence on fossil fuels, the use of animal dung in producing a renewable alternative source of energy has been proved using cow dung. Concerns over the environment and the rising costs for energy and waste water treatment have caused a resurgence of interest in anaerobic treatment and subsequent use of the biogas produced during this treatment of organic wastes as fuel. Biogas from manure wastes has become a potential renewable energy source for both domestic and commercial usage especially in West Nusa Tenggara. This study aims to investagate the quality and quantity of biogas produced from animal dung. The Cows, buffaloes and horses dung were used in this research using anaerobic biotank proses. The animal dungs were digested in ambient temperature and the water composition of degester was also analysed. The result shows that total volume of biogas produced by horse dung is 577.735 liters, and then cow dung is 373.839 liters, and the smallest production generated by buffalo dung which is 352.975 liters. Moreover, biogas from horse dungs generated the highest power of combustion, followed by cow dung, and buffalo dung, 732,425 watt, 556,521 watt 539,759 watt resfectively.